Energizing the thermal conductivity and optical performance of salt hydrate phase change material using copper (II) oxide nano additives for sustainable thermal energy storage - Rajamony, Reji Kumar; Samykano, Mahendran; Kousik Suraparaju, Subbarama; Abd Ghafar, Sofiah Nurhanis; Narayana Namasivayam, Satesh Narayana; Rajkumar, K.; Kadirgama, Kumaran; Devarajan, Ramasamy (EDP Sciences, 2024)
Due to intermittent nature of solar energy, scientists and researchers are working to develop thermal energy storage (TES) systems for effectively use the solar energy. One promising avenue involves utilizing phase change materials (PCMs), but primary challenge lies in their limited thermal conductivity, which results in slower heat transfer rate and lower thermal energy storage density. The present research work demonstrates, to develop and explore a PCM composite by embedding salt hydrate and coper (II) oxide to enhance the heat transfer mechanism for potential utilization of TES material. The optical behavior, and thermal conductivity were analyzed by using Ultraviolet visible spectrum, and thermal property analyzer. The developed copper oxide dispersed PCM composite displayed the thermal conductivity was energized up to 71.5 % without affecting the other properties. Also, the optical absorptance was remarkably enhanced and the transmittance reduced to 87 %. Increasing the concentration of copper oxide nanoparticles in the salt hydrate PCM improves the optical absorptivity and heat conductivity. With these extraordinary abilities the nanocomposite could play a significant role in progress of sustainable TES with significance to contribute towards sustainable development goal of affordable and clean energy and climate change.